Transitional justice in the United States of America : justice for all? - Leyh, Brianne McGonigle (Transitional justice, 2026)
"This book employs a transitional justice lens in order to explore justice initiatives in the United States of America. Transitional justice developed out of societal demands to better address serious abuse, injustice, and atrocities - initially in South American post-authoritarian contexts transitioning to demo-cratic states, and later elsewhere, but especially within post-conflict contexts. The lens of transi-tional justice has only rarely been extended to the United States and never in a comprehensive way. This book aims to provide a contemporary and critical analysis of relevant developments and debates within the United States related to transitional justice. Using the framework of the five main 'pillars' of transitional justice - truth, reparation, accountability, guarantee of non-repetition, and memory - the book identifies and explores relevant justice initiatives, both his-torical and contemporary, across federal, state, and local levels in the United States. The empiri-cal examples taken up show how a broad array of civil society actors are driving transitional justice processes across the country. By recognizing both extraordinary and ordinary justice processes as transitional justice, the book offers a broader understanding of how groups navi-gate transitions to more democratic, peaceful, and socially just societies. The examples further shed light on the expansion of the field to non-traditional contexts, the relationship between global norms and local practices, and the role of law and political compromise. The book con-cludes by emphasizing the value and power of the plurality of initiatives taking shape across the United States but calls for a more coherent transitional justice policy at the national level. This book is relevant for scholars and students with interests in transitional justice, conflict reso-lution, human rights, indigenous studies, culture, and race"-- Provided by publisher.